Recognizing Mental Retardation Early: Detection and Intervention Strategies - Rilta Mardalena; Asra, Yulita Kurniawaty (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2025)
This research confirms that although individuals with intellectual disabilities face significant challenges, they still have developmental potential that can be enhanced through appropriate support and intervention. This research aims to evaluate the effectiveness of interventions on a child with intellectual disabilities who is following a therapy program at the Insan Cemerlang Duri Foundation. The writer used an experiment with a single-subject design (Single Case Experimental Design), which allows for in-depth observation of changes in the subject's behavior before and after treatment. The subject of the study was